Viabilidade técnico-econômica do biodigestor tubular e da energia solar fotovoltaica para geração distribuída na bovinocultura leiteira - Araújo, Gabriela Feistauer (2022)
Dairy cattle activity constitutes an economic activity of great importance in Brazil, in which the State of Paraná has relevant participation. With the aim of reducing production costs, the possibility of generating one’s own electric energy through the distributed generation model seems to be an interesting alternative for the dairy cattle farmer. In this context, two possibilities appear: the use of animal waste as biomass source for biogas production, or the instalation of photovoltaic panels. This work aimed to evaluate and compare through economic tools, such as NPV and Payback, the feasibility of the use of these energy sources in a dairy farm. The results showed the economic feasibility of both energy sources for a 25-year Project horizon, considering a 6,5% minimum attractiveness rate.